Reseña de Casas Gómez, Miguel (dir.) & Rodríguez-Piñero Alcalá (ed.) (2008). X Jornadas de Lingüística - Fernández Smith, Gerard (Pragmalingüística, 2009)
Se trata de Reseña de Casas Gómez, Miguel (dir.) & Rodríguez-Piñero Alcalá (ed.) (2008). X Jornadas de Lingüística.